Class AD modulator for RF polar amplifier - Hou, Rui. (2012)
The power supply modulator is a very critical block of the RF power amplifier (PA) as its performance (including power efficiency, bandwidth and linearity) largely determines the overall performance of the RF PA. In this project, a high speed/high bandwidth Class AD amplifier will be designed as the power supply modulator. Based on the investigation of various amplifier (Class AB& Class D) architectures and operation principle, Class AD amplifier, which takes the advantage of both linearity of Class AB and high power efficiency of Class D will be finally proposed for the RF polar PA.